Supported non-noble metal catalyst as well as preparation method and application thereof

Through the development of non -precious metal catalysts, aluminum oxide carriers, magnesium oxide and titanium dioxide aids, and a variety of non -precious metal active components solved the problem of low existing catalyst ammonia conversion rate and high cost of precious metals, and achieved efficient ammonia decomposition. Hydrogen -making and reducing production costs.

CN119368186AActive Publication Date: 2025-01-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310919858.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-01-28
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

The existing ammonia decomposition hydrogen production catalyst has low ammonia conversion rate and high cost of precious metals, making it difficult to apply on a large scale.

Method used

The development of a load -load non -precious metal catalyst, including alumina, is used as a carrier, magnesium oxide and/or titanium dioxide as the assistant, as well as non -precious metal active components such as iron, cobalt, manganese, copper, zinc, and nickel. Preparation catalysts are prepared through the common precipitation method and baking treatment, and the load capacity of non -precious metal active components and assistants is optimized to regulate the electronics and chemical structures of the catalyst.

Benefits of technology

Increasing the transformation rate of ammonia in the hydrogenation of ammonia, reducing production costs, and optimizing the particle size distribution and surface area of ​​the catalyst, which improves the reaction activity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368186A_ABST
    Figure CN119368186A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen production through ammonia decomposition, and discloses a supported non-noble metal catalyst as well as a preparation method and application thereof. The supported non-noble metal catalyst comprises a carrier, an auxiliary agent and a non-noble metal active component, the carrier is aluminum oxide, the auxiliary agent is magnesium oxide and / or titanium dioxide, and the non-noble metal active component comprises at least one of iron, cobalt, manganese, copper and zinc and nickel; on the basis of the total amount of the carrier, the loading amount of the non-noble metal active component in terms of oxide is 0.5-20% by mass; in terms of oxide, the ratio of the loading capacity of at least one of iron, cobalt, manganese, copper and zinc to the loading capacity of nickel is (0.2-5): 1; and the particle size distribution of the non-noble metal active component in the catalyst is 20-100 nm. The catalyst can improve the conversion rate of ammonia in hydrogen production through ammonia decomposition, and the production cost is reduced by replacing noble metal with non-noble metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen production by decomposing ammonia, and in particular to a supported non-precious metal catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of the hydrogen energy industry, the development of efficient, safe and low-cost hydrogen storage and transportation methods has gradually become a key issue that needs to be urgently addressed. Current hydrogen storage technologies mainly include gaseous hydrogen storage, liquid hydrogen storage and solid hydrogen storage. Among them, gaseous hydrogen storage requires higher pressure, high energy consumption and limited capacity. There are unsafe factors such as hydrogen leakage and container explosion during storage and transportation. Liquid hydrogen storage is mainly divided into liquid hydrogen and liquid hydrogen storage carriers. Hydrogen liquefaction requires low temperature (down to about -253°C), and hydrogen volatilization is serious and energy consumption is high during the liquefaction process. In comparison, ammonia has obvious advantages as a hydrogen storage medium, mainly including the following aspects: (1) Ammonia can be liquefied at -33°C under standard atmospheric pressure, with low energy consumption; (2) Liquid ammonia has high energy density, with a mass hydrogen storage capacity of 17wt%, and a volume hydrogen storage density that is 1.7 times higher than that of liquid hydrogen, which is also much higher than the current mainstream high-pressure long-tube trailer method of storing and transporting hydrogen; (3) Compared with organic liquid hydrogen storage, the hydrogen obtained by decomposition of ammonia has high purity and no carbon emissions during the process; (4) Using ammonia as a hydrogen storage medium, its comprehensive cost for long-distance transportation is lower than that of liquid hydrogen and organic liquid hydrogen carriers; (5) There is currently a mature ammonia synthesis and liquid ammonia transportation network, which is conducive to promoting the rapid development of the hydrogen storage and transportation industry.

[0003] The high activation energy and slow kinetics of ammonia decomposition limit its practical application. The core technology for achieving the "hydrogen-ammonia-hydrogen" conversion lies in the development of efficient ammonia decomposition catalysts. Ammonia decomposition hydrogen production catalysts are mainly supported metal materials. For example, researchers from Tsinghua University and Hong Kong Baptist University jointly developed a Ru / Al2O3 catalyst. By adding Na as an additive to optimize the electronic environment around Ru, the ammonia decomposition conversion rate reached 73.7% at a reaction temperature of 550°C. However, precious metals are expensive and difficult to use on a large scale. Therefore, it is of great significance to explore non-precious metal catalysts with both high activity and low cost for ammonia decomposition hydrogen production. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of low ammonia conversion rate of ammonia decomposition hydrogen production catalyst in the prior art, and to provide a supported non-precious metal catalyst and its preparation method and application, which can improve the ammonia conversion rate in ammonia decomposition hydrogen production and use non-precious metals to replace precious metals to reduce production costs.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a supported non-precious metal catalyst, wherein the catalyst comprises a carrier, an auxiliary agent and a non-precious metal active component, the carrier is alumina, the auxiliary agent is magnesium oxide and / or titanium dioxide, and the non-precious metal active component comprises at least one of iron, cobalt, manganese, copper and zinc and nickel; based on the total amount of the carrier, the loading amount of the non-precious metal active component in terms of oxide is 0.5-20% by mass; in terms of oxide, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel is (0.2-5):1; the particle size distribution of the non-precious metal active component in the catalyst is 20-100nm.

[0006] The second aspect of the present invention provides a method for preparing a supported non-precious metal catalyst, wherein the method comprises: using a coprecipitation method, in the presence of a precipitant, a dispersion containing a carrier precursor and an auxiliary agent and a solution containing a non-precious metal active component precursor are subjected to a coprecipitation reaction, and then calcined to obtain the supported non-precious metal catalyst;

[0007] The carrier is alumina, the additive is magnesium oxide and / or titanium dioxide, and the non-precious metal active component includes at least one of iron, cobalt, manganese, copper and zinc and nickel;

[0008] The amounts of the carrier precursor, the non-precious metal active component precursor and the auxiliary agent are such that the loading amount of the non-precious metal active component in the prepared catalyst is 0.5-20% by mass in terms of oxide, based on the total amount of the carrier;

[0009] The amount of the non-precious metal active component precursor is such that in the prepared catalyst, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel, calculated as oxide, is (0.2-5):1.

[0010] The third aspect of the present invention provides a supported non-precious metal catalyst prepared by the preparation method described in the second aspect.

[0011] The fourth aspect of the present invention provides a use of the supported non-precious metal catalyst described in the first aspect or the third aspect in ammonia decomposition hydrogen production reaction.

[0012] Due to the adoption of the above technical solution, compared with the prior art, the advantages of the present invention are:

[0013] 1. The catalyst used in the present invention does not require the addition of precious metals, has low cost, and the carrier is cheap, the preparation process is simple, the repeatability is good, and it is easy to scale up production;

[0014] 2. Utilize the synergistic effect between multi-metal active centers and add additives to adjust their electronic and chemical structures, optimize the adsorption and desorption of NH3 molecules and nitrogen-containing reaction intermediates by the active centers, thereby reducing the activation energy of ammonia decomposition and accelerating the reaction rate; at the same time, multiple non-precious metals can cooperate with each other to replace precious metals to reduce production costs;

[0015] 3. Pseudo-boehmite is selected as a precursor to load non-precious metals, and then calcined to form an alumina carrier, which helps to promote the uniform dispersion of metal centers on the carrier, while forming a strong metal-carrier interaction, thereby improving the ammonia decomposition activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the X-ray diffraction pattern (XRD) of the supported non-precious metal catalyst of Example 1 of the present invention. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] In the present invention, it can be understood that the particle size distribution is used to represent the dispersion of non-precious metal active components on the catalyst carrier, which is measured by counting high-resolution transmission electron microscopy images and calculating the average particle size, for example, by randomly measuring 30-50 grain sizes and then calculating the average value.

[0019] In the present invention, the specific surface area of ​​the catalyst is measured by the BET method. The specific test conditions are: using a fully automatic specific surface area and porosity analyzer, and pretreating the sample at 150° C. and vacuum conditions for 12 hours before the adsorption test.

[0020] In the present invention, the resistivity of the catalyst is measured by electrochemical impedance spectroscopy. The specific test conditions are: using an electrochemical workstation for measurement and a three-electrode system (the working electrode is the prepared sample, the counter electrode is a platinum wire, and the reference electrode is silver / silver chloride), and the electrolyte is a 0.2M Na2SO4 solution. The method for preparing the working electrode is: 10 mg of the sample is dispersed in 1.5 mL of ethanol, and after ultrasonic dispersion for 2 hours, it is spin-coated on FTO conductive glass (specifications 2 cm×2.5 cm) using a spin coater, using 200 microliters of dispersion each time, and a total of 6 spin coatings. Tested at open circuit voltage, the disturbance is 10 mV, and the test frequency range is 0.01 Hz-10 5 Hz.

[0021] In the present invention, the loading amount of each component in the catalyst is calculated by the feeding amount.

[0022] In the present invention, it should be noted that, in the catalyst composition, iron oxide is calculated as Fe2O3, Ni oxide is calculated as NiO, cobalt oxide is calculated as Co3O4, copper oxide is calculated as CuO, and zinc oxide is calculated as ZnO.

[0023] The first aspect of the present invention provides a supported non-precious metal catalyst, wherein the catalyst comprises a carrier, an auxiliary agent and a non-precious metal active component, the carrier is aluminum oxide, the auxiliary agent is magnesium oxide and / or titanium dioxide, the non-precious metal active component comprises at least one of iron, cobalt, manganese, copper and zinc and nickel; based on the total amount of the carrier, the loading amount of the non-precious metal active component in terms of oxide is 0.5-20% by mass; in terms of oxide, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel is (0.2-5):1; the particle size distribution of the non-precious metal active component in the catalyst is 20-100 nm.

[0024] The advantage of adopting this preferred embodiment is that it is helpful to promote the adsorption and dissociation of reactants on the active center.

[0025] In the present invention, the non-precious metal active components and the loading amount of the auxiliary agent are adjusted, and the non-precious metal active components cooperate to adjust the reaction activity of the catalyst. Preferably, based on the weight of the carrier, the loading amount of the non-precious metal active component in terms of oxide is 5-15% by mass, and the loading amount of the auxiliary agent is 1-10% by mass.

[0026] In the present invention, preferably, in terms of oxide, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel is (0.5-2): 1. The advantage of adopting this preferred embodiment is to adjust the active metal composition to control the metal-metal interaction and optimize the adsorption and activation of the active center on the reactant molecules.

[0027] In the present invention, by selecting the type of non-precious metal active component as the active center of the catalyst, the same synergistic effect between multiple non-precious metal centers can improve the reaction activity of the catalyst, and at the same time, multiple non-precious metals cooperate with each other to replace precious metals to reduce production costs. Preferably, the non-precious metal active component includes iron and / or cobalt and nickel, and more preferably iron, cobalt and nickel.

[0028] In the present invention, preferably, based on the total amount of the carrier, the loading amount of nickel calculated as oxide is 1-10% by mass, preferably 2-8% by mass, the loading amount of iron calculated as oxide is 1-6% by mass, preferably 1-2% by mass, and the loading amount of cobalt calculated as oxide is 1-5% by mass, preferably 2-4% by mass. The advantage of adopting this preferred embodiment is that by optimizing the metal composition, abundant dislocation interfaces between metal lattices are formed, providing abundant active centers to increase the reaction rate.

[0029] In the present invention, the dispersion of the catalyst is improved by the coordination between the non-precious metal active component and the carrier. Preferably, the particle size distribution of the non-precious metal active component on the catalyst is 30-50 nm. The advantages of adopting this preferred embodiment are to control the size of the active metal to increase the number of surface active sites, inhibit the aggregation and deactivation of the active metal during the reaction due to too small particle size, and avoid reducing the metal utilization rate due to too large particles.

[0030] In the present invention, preferably, the specific surface area of ​​the catalyst is 300-400m 2 / g, more preferably 350-400m 2 The advantage of adopting this preferred embodiment is that it promotes the diffusion and migration of reactant and product molecules, and is beneficial to the contact between reactant molecules and active centers.

[0031] In the present invention, preferably, the resistivity of the catalyst is 200-800Ω·m, more preferably 300-600Ω·m. The advantage of adopting this preferred embodiment is that it is conducive to charge migration and improves reaction efficiency.

[0032] The second aspect of the present invention provides a method for preparing a supported non-precious metal catalyst, wherein the method comprises: using a coprecipitation method, in the presence of a precipitant, a dispersion containing a carrier precursor and an auxiliary agent and a solution containing a non-precious metal active component precursor are subjected to a coprecipitation reaction, and then calcined to obtain the supported non-precious metal catalyst;

[0033] The carrier is alumina, the additive is magnesium oxide and / or titanium dioxide, and the non-precious metal active component includes at least one of iron, cobalt, manganese, copper and zinc and nickel;

[0034] The amounts of the carrier precursor, the non-precious metal active component precursor and the auxiliary agent are such that the loading amount of the non-precious metal active component in the prepared catalyst is 0.5-20% by mass in terms of oxide, based on the total amount of the carrier;

[0035] The amount of the non-precious metal active component precursor is such that in the prepared catalyst, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel, calculated as oxide, is (0.2-5):1.

[0036] The method provided by the invention has simple synthesis steps, and the synthesized catalyst exhibits excellent catalytic activity for decomposing ammonia, and has broad application prospects.

[0037] In the present invention, preferably, the amounts of the carrier precursor, the non-precious metal active component precursor and the auxiliary agent are such that in the prepared catalyst, based on the total amount of the carrier, the loading amount of the non-precious metal active component in terms of oxide is 5-15% by mass, and the loading amount of the auxiliary agent is 1-10% by mass.

[0038] In the present invention, preferably, the amount of the non-precious metal active component precursor used is such that in the prepared catalyst, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel, calculated as oxide, is (0.5-2):1.

[0039] In the present invention, the types of non-precious metal active components have been described in the first aspect and will not be described in detail here.

[0040] In the present invention, preferably, the amount of the non-precious metal active component precursor used is such that in the prepared catalyst, based on the total amount of the carrier, the nickel loading as oxide is 1-10% by mass, preferably 2-8% by mass, the iron loading as oxide is 1-6% by mass, preferably 1-2% by mass, and the cobalt loading as oxide is 1-5% by mass, preferably 2-4% by mass.

[0041] In the present invention, preferably, the carrier precursor is selected from at least one of pseudo-boehmite, aluminum nitrate, aluminum chloride, and aluminum sulfate, preferably pseudo-boehmite. The advantage of adopting this preferred embodiment is that it is conducive to providing an alkaline carrier environment, promoting the reaction bottleneck step rate, and improving the reaction activity.

[0042] In the present invention, preferably, the dispersion containing the carrier precursor and the auxiliary agent is prepared by dispersing the carrier precursor and the auxiliary agent in water.

[0043] In the present invention, preferably, the mass ratio of support precursor: auxiliary agent: water calculated as alumina is 1:0.01-0.1:1-5.

[0044] In the present invention, preferably, the non-precious metal active component precursor is selected from soluble compounds of each non-precious metal active component, preferably at least one of chloride, nitrate, sulfate and acetylacetonate. The present invention does not limit its specific type, and those skilled in the art can select it according to actual needs.

[0045] In the present invention, preferably, the solution containing the non-precious metal active component is prepared by dissolving a non-precious metal active component precursor in water.

[0046] In the present invention, preferably, the mass ratio of the non-precious metal active component precursor to water is 5:1-1:5.

[0047] In the present invention, there is no particular limitation on the order of adding the carrier precursor, the auxiliary agent and the non-precious metal component. According to a specific embodiment of the present invention, the preparation method of the supported non-precious metal catalyst comprises: dissolving the carrier precursor and the auxiliary agent in water to obtain a dispersion containing the carrier precursor and the auxiliary agent, then dissolving the non-precious metal active component in water to obtain a solution containing the non-precious metal active component, and dropping the dispersion containing the carrier precursor and the auxiliary agent into the solution containing the non-precious metal active component, and finally adding a precipitant to perform a co-precipitation reaction and then calcining to obtain a supported non-precious metal catalyst.

[0048] In the present invention, there is no particular limitation on the type of the precipitant, and it can be any precipitant conventionally defined in the art. Preferably, the precipitant is selected from at least one of potassium hydroxide, sodium hydroxide, ammonia water, potassium carbonate, sodium carbonate and ammonium carbonate.

[0049] In the present invention, preferably, the concentration of the precipitant is 0.5-10 mol / L, preferably 2-8 mol / L.

[0050] In the present invention, preferably, the molar ratio of the precipitant to the non-precious metal active component precursor is 6:1-2:1.

[0051] In the present invention, there is no particular limitation on the conditions of the coprecipitation reaction. Preferably, the conditions of the coprecipitation reaction include: a temperature of 20-80°C and a time of 2-24 hours. Preferably, the conditions of the coprecipitation reaction include: a temperature of 40-60°C and a time of 8-16 hours. The advantage of adopting this preferred embodiment is to promote the growth and dispersion of non-precious metal active centers on the carrier and improve the reaction activity.

[0052] In the present invention, there is no particular limitation on the calcination conditions. Preferably, the calcination conditions include: a calcination temperature of 300-800°C, a time of 0.5-12h, and a heating rate of 2-20°C / min; more preferably, a calcination temperature of 500-700°C, a time of 2-6h, and a heating rate of 2-10°C / min.

[0053] In the present invention, the calcination is carried out under a protective atmosphere, and the protective atmosphere is an inert gas and / or nitrogen. The type of the inert gas is not specifically limited in the present invention.

[0054] The third aspect of the present invention provides a supported non-precious metal catalyst prepared by the preparation method described in the second aspect.

[0055] The fourth aspect of the present invention provides an application of the supported non-precious metal catalyst described in the first aspect or the third aspect in ammonia decomposition hydrogen production reaction. Preferably, the supported non-precious metal catalyst described in the first aspect or the third aspect is contacted with a feed gas for reaction.

[0056] In the present invention, preferably, the raw gas comprises 3-15 volume % of ammonia and 85-97 volume % of protective gas.

[0057] In the present invention, preferably, the protective gas is an inert atmosphere, for example, it can be any one of argon, helium and neon, and the present invention does not make any specific limitation on this.

[0058] In the present invention, preferably, the application conditions include: a temperature of 500-600° C. and a mass space velocity of 10000-20000 mL / (g min).

[0059] The present invention will be described in detail below by way of examples. In the following examples, the raw materials are all commercially available unless otherwise specified.

[0060] In the following examples and comparative examples, the conversion rate of ammonia is calculated by the following formula:

[0061] Ammonia conversion rate (%) = (inlet ammonia concentration - outlet ammonia concentration) / outlet ammonia concentration * 100%.

[0062] Example 1

[0063] Weigh 62.5g of pseudo-boehmite (solid content 80%) and 2.5g of magnesium oxide, mix and evenly disperse in 100mL of water, weigh 10.0g of nickel nitrate hexahydrate, 5.0g of iron nitrate nonahydrate and 5.4g of cobalt nitrate hexahydrate, dissolve in 20mL of water, and add dropwise the dispersion containing pseudo-boehmite and magnesium oxide, take 20mL of 5.0mol / L NaOH solution and add dropwise the above mixture, stir at 50°C for 12 hours. After the obtained solid is recovered, it is calcined in a muffle furnace at 600°C for 4 hours, with a heating rate of 5°C / min, and the supported non-precious metal catalyst is obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2. Figure 1 This is the XRD diagram of the supported non-precious metal catalyst. It can be seen that the sample has a high degree of crystallinity and contains no other impurities except the alumina support and metal active centers.

[0064] Example 2

[0065] 62.5g of pseudo-boehmite (solid content 80%) and 1.5g of magnesium oxide were weighed and mixed and uniformly dispersed in 100mL of water, 4.0g of nickel nitrate hexahydrate, 2.5g of iron nitrate nonahydrate and 5.4g of cobalt nitrate hexahydrate were weighed and dissolved in 20mL of water, and the dispersion containing pseudo-boehmite and magnesium oxide was added dropwise, 20mL of NaOH solution with a concentration of 5.0mol / L was taken and added dropwise to the above mixed solution, and stirred at 40°C for 8 hours. After the obtained solid was recovered, it was calcined in a muffle furnace at 500°C for 3 hours, with a heating rate of 4°C / min, and the supported non-precious metal catalyst was obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0066] Example 3

[0067] 62.5g of pseudo-boehmite (solid content 80%) and 3.0g of magnesium oxide were weighed and mixed and uniformly dispersed in 100mL of water, 15.6g of nickel nitrate hexahydrate, 5.0g of iron nitrate nonahydrate and 3.6g of cobalt nitrate hexahydrate were weighed and dissolved in 20mL of water, and the dispersion containing pseudo-boehmite and magnesium oxide was added dropwise, 20mL of NaOH solution with a concentration of 5.0mol / L was taken and added dropwise to the above mixed solution, and stirred at 60°C for 26 hours. The obtained solid was recovered and calcined in a muffle furnace at 700°C for 6 hours, with a heating rate of 8°C / min, and the supported non-precious metal catalyst was obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0068] Example 4

[0069] 62.5g of pseudo-boehmite (solid content 80%) and 2.5g of magnesium oxide were weighed and mixed and uniformly dispersed in 100mL of water, 2.0g of nickel nitrate hexahydrate, 5.0g of iron nitrate nonahydrate and 5.4g of cobalt nitrate hexahydrate were weighed and dissolved in 20mL of water, and the dispersion containing pseudo-boehmite and magnesium oxide was added dropwise, 20mL of 5.0mol / L NaOH solution was taken and added dropwise to the above mixed solution, and stirred at 50°C for 12 hours. The obtained solid was recovered and calcined in a muffle furnace at 600°C for 4 hours, with a heating rate of 5°C / min, and the supported non-precious metal catalyst was obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0070] Example 5

[0071] 62.5g of pseudo-boehmite (solid content 80%) and 0.5g of magnesium oxide were weighed and mixed and uniformly dispersed in 100mL of water, 19.5g of nickel nitrate hexahydrate, 12.6g of iron nitrate nonahydrate and 5.4g of cobalt nitrate hexahydrate were weighed and dissolved in 40mL of water, and the dispersion containing pseudo-boehmite and magnesium oxide was added dropwise, 40mL of NaOH solution with a concentration of 5.0mol / L was taken and added dropwise to the above mixed solution, and stirred at 50°C for 12 hours. After the obtained solid was recovered, it was calcined in a muffle furnace at 600°C for 4 hours, with a heating rate of 5°C / min, and the supported non-precious metal catalyst was obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0072] Example 6

[0073] Weigh 62.5g of pseudo-boehmite (solid content 80%) and 1.5g of titanium dioxide, mix and evenly disperse in 100mL of water, weigh 10.0g of nickel nitrate hexahydrate, 5.0g of ferric nitrate nonahydrate and 5.4g of cobalt nitrate hexahydrate, dissolve in 20mL of water, and add dropwise the dispersion containing pseudo-boehmite and titanium dioxide, take 20mL of 5.0mol / L NaOH solution and add dropwise the above mixture, stir at 80°C for 2 hours. After the obtained solid is recovered, it is calcined at 600°C in a muffle furnace for 4 hours, with a heating rate of 5°C / min, and the supported non-precious metal catalyst is obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0074] Example 7

[0075] Weigh 62.5g of pseudo-boehmite (solid content 80%) and 3.0g of titanium dioxide, mix and evenly disperse in 100mL of water, weigh 8.0g of nickel nitrate hexahydrate, 5.0g of ferric nitrate nonahydrate and 5.4g of cobalt nitrate hexahydrate, dissolve in 20mL of water, and add dropwise the dispersion containing pseudo-boehmite and titanium dioxide, take 20mL of 5.0mol / L KOH solution and add dropwise the above mixture, stir at 50°C for 12 hours. After the obtained solid is recovered, it is calcined in a muffle furnace at 800°C for 24 hours, with a heating rate of 10°C / min, and the supported non-precious metal catalyst is obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0076] Example 8

[0077] 62.5g of pseudo-boehmite (solid content 80%) and 2.5g of magnesium oxide were weighed and mixed and uniformly dispersed in 100mL of water, 10.0g of nickel nitrate hexahydrate, 3.0g of copper nitrate trihydrate and 5.4g of zinc nitrate hexahydrate were weighed and dissolved in 30mL of water, and the dispersion containing pseudo-boehmite and magnesium oxide was added dropwise, 20mL of NaOH solution with a concentration of 5.0mol / L was taken and added dropwise to the above mixed solution, and stirred at 50°C for 12 hours. The obtained solid was recovered and calcined in a muffle furnace at 600°C for 4 hours, with a heating rate of 5°C / min, and the supported non-precious metal catalyst was obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0078] Example 9

[0079] Weigh 62.5g of pseudo-boehmite (solid content 80%) and 2.5g of magnesium oxide, mix and evenly disperse in 100mL of water, weigh 10.0g of nickel nitrate hexahydrate and 5.0g of ferric nitrate nonahydrate, dissolve in 20mL of water, and add dropwise the dispersion containing pseudo-boehmite and magnesium oxide, take 20mL of 5.0mol / L NaOH solution and add dropwise the above mixture, and stir at 50°C for 12 hours. After the obtained solid is recovered, it is calcined in a muffle furnace at 500°C for 4 hours, with a heating rate of 5°C / min, and the supported non-precious metal catalyst is obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0080] Comparative Example 1

[0081] Weigh 62.5g of pseudo-boehmite (solid content 80%) and evenly disperse it in 100mL of water, weigh 10.0g of nickel nitrate hexahydrate, 4.0g of iron nitrate nonahydrate and 5.4g of cobalt nitrate hexahydrate and dissolve them in 20mL of water, and add the dispersion containing pseudo-boehmite dropwise, take 20mL of 5.0mol / L NaOH solution and add the above mixed solution dropwise, and stir at 50°C for 12 hours. After the obtained solid is recovered, it is calcined in a muffle furnace at 600°C for 4 hours, with a heating rate of 5°C per minute, and the supported non-precious metal catalyst is obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0082] Comparative Example 2

[0083] 62.5 g of pseudo-boehmite (solid content 80%) and 2.5 g of magnesium oxide were weighed and mixed and uniformly dispersed in 100 mL of water, 19.5 g of nickel nitrate hexahydrate was weighed and dissolved in 20 mL of water, and the dispersion containing pseudo-boehmite and magnesium oxide was added dropwise, 20 mL of 5.0 mol / L NaOH solution was taken and added dropwise to the above mixed solution, and stirred at 50° C. for 12 hours. The obtained solid was recovered and calcined in a muffle furnace at 600° C. for 4 hours, with a heating rate of 5° C. / min, and the supported non-precious metal catalyst was obtained after cooling to room temperature. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0084] Comparative Example 3

[0085] Weigh 62.5g of pseudo-boehmite (solid content 80%) and 2.5g of magnesium oxide, mix them and roast them at 600°C in a muffle furnace for 4 hours at a heating rate of 5°C / min to obtain a mixture of an additive and a carrier. Weigh 10.0g of nickel nitrate hexahydrate, 5.0g of ferric nitrate nonahydrate and 5.4g of cobalt nitrate hexahydrate, dissolve them in 20mL of water, add the mixture of the additive and the carrier, and immerse them for 12 hours. Recover the solid and roast it at 600°C in a muffle furnace for 4 hours at a heating rate of 5°C / min. After cooling to room temperature, the supported non-precious metal catalyst is obtained. The catalyst composition is shown in Table 1, and the catalyst properties are shown in Table 2.

[0086] Ammonia decomposition hydrogen production activity test

[0087] The above examples and comparative examples were tested for the activity of hydrogen production by ammonia decomposition using a fixed bed microreactor, the feed gas was a 15 volume % NH3 / Ar mixed gas, the mass space velocity was 12000 mL / (g min), the catalyst loading was 1.0 g, the proportion of quartz sand was 4.0 g, the reaction temperature was 550°C, the outlet gas composition was analyzed using an infrared detector and a chromatogram, and the catalyst activity is shown in Table 3.

[0088] Table 1

[0089] Catalyst composition Example 1 <![CDATA[5wt%NiO-2wt%Fe2O3-3wt%Co3O4,5wt%MgO]]> Example 2 <![CDATA[2wt%NiO-1wt%Fe2O3-3wt%Co3O4,3wt%MgO]]> Example 3 <![CDATA[8wt%NiO-2wt%Fe2O3-2wt%Co3O4,6wt%MgO]]> Example 4 <![CDATA[1wt%NiO-2wt%Fe2O3-3wt%Co3O4,5wt%MgO]]> Example 5 <![CDATA[10wt%NiO-5wt%Fe2O3-3wt%Co3O4,1wt%MgO]]> Example 6 <![CDATA[5wt%NiO-2wt%Fe2O3-3wt%Co3O4,3wt%TiO2]]> Example 7 <![CDATA[4wt%NiO-2wt%Fe2O3-3wt%Co3O4,6wt%TiO2]]> Example 8 5wt%NiO-2wt%CuO-3wt%ZnO, 5wt%MgO Example 9 <![CDATA[5wt%NiO-2wt%Fe2O3,5wt%MgO <!-- 7 -->]]> Comparative Example 1 <![CDATA[5wt%NiO-2wt%Fe2O3-3wt%Co3O4]]> Comparative Example 2 10wt%NiO, 5wt%MgO Comparative Example 3 <![CDATA[5wt%NiO-2wt%Fe2O3-3wt%Co3O4,5wt%MgO]]>

[0090] Note: In Table 1, the loading amount of each component is based on the total amount of the carrier.

[0091] Table 2

[0092]

[0093]

[0094] Table 3

[0095] Reaction temperature (℃) Conversion rate (%) Example 1 550 99.5 Example 2 550 98.5 Example 3 550 97.5 Example 4 550 88.4 Example 5 550 89.6 Example 6 550 92.4 Example 7 550 89.0 Example 8 550 88.5 Example 9 550 87.2 Comparative Example 1 550 82.5 Comparative Example 2 550 81.3 Comparative Example 3 550 52.5

[0096] It can be seen from the results in Table 3 that the preferred embodiments 1-3 of the present invention have significantly better ammonia decomposition effects.

[0097] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A supported non-precious metal catalyst, characterized in that: The catalyst comprises a carrier, an auxiliary agent and a non-precious metal active component, wherein the carrier is alumina, the auxiliary agent is magnesium oxide and / or titanium dioxide, and the non-precious metal active component comprises at least one of iron, cobalt, manganese, copper and zinc and nickel; based on the total amount of the carrier, the loading amount of the non-precious metal active component in terms of oxide is 0.5-20% by mass; in terms of oxide, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel is (0.2-5):1; the particle size distribution of the non-precious metal active component in the catalyst is 20-100 nm.

2. The catalyst according to claim 1, wherein Based on the total amount of the carrier, the loading amount of the non-precious metal active component in terms of oxide is 5-15% by mass, and the loading amount of the auxiliary agent is 1-10% by mass; Preferably, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel is (0.5-2):1, calculated as oxide; Preferably, the non-precious metal active component comprises iron and / or cobalt and nickel, more preferably iron, cobalt and nickel; Preferably, based on the total amount of the carrier, the loading amount of nickel calculated as oxide is 1-10 mass %, preferably 2-8 mass %, the loading amount of iron calculated as oxide is 1-6 mass %, preferably 1-2 mass %, and the loading amount of cobalt calculated as oxide is 1-5 mass %, preferably 2-4 mass %.

3. The catalyst according to claim 1 or 2, wherein The particle size distribution of the non-precious metal active component on the catalyst is 30-50 nm; Preferably, the specific surface area of ​​the catalyst is 300-400m 2 / g, more preferably 350-400m 2 / g; Preferably, the resistivity of the catalyst is 200-800Ω·m, more preferably 300-600Ω·m.

4. A method for preparing a supported non-precious metal catalyst, wherein: The method comprises: using a coprecipitation method, in the presence of a precipitant, coprecipitating a dispersion containing a carrier precursor and an auxiliary agent with a solution containing a non-precious metal active component precursor, and then calcining to obtain the supported non-precious metal catalyst; The carrier is alumina, the additive is magnesium oxide and / or titanium dioxide, and the non-precious metal active component includes at least one of iron, cobalt, manganese, copper and zinc and nickel; The amounts of the carrier precursor, the non-precious metal active component precursor and the auxiliary agent are such that the loading amount of the non-precious metal active component in the prepared catalyst is 0.5-20% by mass in terms of oxide, based on the total amount of the carrier; The amount of the non-precious metal active component precursor is such that in the prepared catalyst, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel, calculated as oxide, is (0.2-5):

1.

5. The method according to claim 4, wherein: The amounts of the carrier precursor, the non-precious metal active component precursor and the auxiliary agent are such that in the prepared catalyst, the loading amount of the non-precious metal active component in terms of oxide is 5-15% by mass, and the loading amount of the auxiliary agent is 1-10% by mass, based on the total amount of the carrier; Preferably, the amount of the non-precious metal active component precursor is such that in the prepared catalyst, the ratio of the loading amount of at least one of the iron, cobalt, manganese, copper and zinc to the loading amount of the nickel, calculated as oxide, is (0.5-2):1; Preferably, the non-precious metal active component comprises iron and / or cobalt and nickel, more preferably iron, cobalt and nickel; Preferably, the amount of the non-precious metal active component precursor is such that in the prepared catalyst, based on the total amount of the carrier, the nickel loading as oxide is 1-10% by mass, preferably 2-8% by mass, the iron loading as oxide is 1-6% by mass, preferably 1-2% by mass, and the cobalt loading as oxide is 1-5% by mass, preferably 2-4% by mass.

6. The method according to claim 4 or 5, wherein: The carrier precursor is selected from at least one of pseudo-boehmite, aluminum nitrate, aluminum chloride and aluminum sulfate, preferably pseudo-boehmite; And / or, the non-precious metal active component precursor is selected from soluble compounds of various non-precious metal active components, preferably at least one of chloride, nitrate, sulfate and acetylacetonate.

7. The method according to claim 4 or 5, wherein: The precipitant is selected from at least one of potassium hydroxide, sodium hydroxide, ammonia water, potassium carbonate, sodium carbonate and ammonium carbonate; and / or, the concentration of the precipitant is 0.5-10 mol / L; and / or, the molar ratio of the precipitant to the non-precious metal active component precursor is 6:1-2:1; And / or, the coprecipitation reaction conditions include: temperature of 20-80°C, time of 2-24h; Preferably, the coprecipitation reaction conditions include: temperature of 40-60° C. and time of 8-16 h.

8. The method according to claim 4 or 5, wherein: The calcination conditions include: calcination temperature of 300-800°C, time of 0.5-12h, and heating rate of 2-20°C / min; more preferably, calcination temperature of 500-700°C, time of 2-6h, and heating rate of 2-10°C / min.

9. A supported non-precious metal catalyst obtained according to the preparation method described in any one of claims 4 to 8.

10. Use of the supported non-precious metal catalyst according to any one of claims 1 to 3 and 9 in ammonia decomposition hydrogen production reaction; Preferably, the application conditions include: The temperature is 500-600°C, and the mass space velocity is 10000-20000 mL / (gmin).

Citation Information

Patent Citations

  • Supported type nickel catalyst for producing hydrogen from decomposition of ammonia and preparation method

    CN101352685A

  • Bimetal methanation catalyst and preparation method thereof

    CN101703933A

  • Non-noble metal catalyst for hydrogen production through dehydrogenation of organic matters and preparation method and application thereof

    CN111889093A

  • Magnesium oxide modified aluminum oxide loaded bimetallic nickel-cobalt catalyst as well as preparation method and application thereof

    CN115888719A

  • Hydrogenation catalyst as well as preparation method and application thereof

    CN116408089A